The role of GPD1L, a sodium channel interacting gene, in the pathogenesis of Brugada Syndrome - Greiner, Alexander M.; Mehdi, Haider; Cevan, Chloe; Gutmann, Rebecca; London, Barry (Frontiers in Medicine, 2024)
Background Brugada Syndrome (BrS) is an inherited arrhythmia syndrome in which mutations in the cardiac sodium channel SCN5A (NaV1.5) account for approximately 20% of cases. Mutations in sodium channel-modifying genes may account additional BrS cases, though BrS may be polygenic given common SNPs associated with BrS have been identified. Recent analysis, however, has suggested that SCN5A should be regarded as the sole monogenic cause of BrS. Objective We sought to re-assess the genetic underpinnings of BrS in a large mutligenerational family with a putative mutation in GPD1L that affect surface membrane expression of NaV1.5 in vitro. Methods Fine linkage mapping was performed in the family using the Illumina Global Screening array. Whole exome sequencing of the proband was performed to identify rare variants and mutations, and Sanger sequencing was used to assay previously-reported risk single nucleotide polymorphsims (SNPs) for BrS. Results Linkage analysis decreased the size of the previously-reported microsatellite linkage region to approximately 3 megabases. GPD1L-A280V was the only coding non-synonymous variation present at <1% allele frequency in the proband within the linkage region. No rare nonsynonymous variants were present outside the linkage area in affected individuals in genes associated with BrS. Risk SNPs known to predispose to BrS were overrepresented in affected members of the family. Conclusion Together, our data suggest GPD1L-A280V remains the most likely cause of BrS in this large multigenerational family. While care should be taken in interpreting variant pathogenicity given the genetic uncertainty of BrS, our data support inclusion of other putative BrS genes in clinical genetic panels.